Dynamic transcriptome and metabolome analyses of two sweet corn lines under artificial aging treatment - Zili Zhang; Ruichun Yang; Lei Gao; Shilin Huang; Feng Jiang; Qingchun Chen; Pengfei Liu; Faqiang Feng (BMC Genomics)
Abstract Background Strong tolerance to seed aging is an important agricultural trait for sweet corn production. Previous studies have primarily focused on the QTLs for the seed vigor. However, there were few researches involving in the metabolome and transcriptome of artificial aging seeds. Results Using two inbred lines with significant differences in seed artificial aging tolerance, RNA sequencing and non-targeted metabolomic analysis were employed to extensively evaluate transcripts and metabolites in seeds that underwent artificial aging. Fourteen common transcripts and 16 common metabolites with sustained differential expression were identified in the two lines, suggesting their potential necessity in seed response to artificial aging. Enrichment analysis of differentially expressed genes (DEGs) in the transcriptome at different stages revealed significant enrichment KEGG pathways, “Oxidative phosphorylation” was the common pathway in the 0d vs 3d comparison for K107 and L155. The identical enriched KEGG pathways were observed in the 3d vs 6d comparison for K107 and 0d vs 6d comparison for L155, indicating a slower transcriptomic response in the aging-tolerance line. DEGs at 0 days between the two lines had been enriched in the “Terpenoid backbone biosynthesis” and “Ribosome” pathways, while at 6 days, the enrichment pathway were “Sulfur metabolism”, “Linoleic acid metabolism”, and “Plant hormone signal transduction”. A total of 312 differentially expressed metabolites (DEMs) were found at 0, 3 and 6 days after seed aging treatment, and they shared enriched metabolic pathway of “ABC transporters”. The KEGG enrichment of DEGs and DEMs shared the common pathway, namely “Linoleic acid metabolism”. Among these, the most abundant metabolites were Glutathione, Adenosine, Trehalose, and 10E,12Z-Octadecadienoic acid. Focusing on the ascorbate–glutathione pathway revealed that the difference in ROS production and the ROS scavenging capability mediated by glutathione S-transferase (GST) genes were important factors contributing to the differing seed aging tolerance in the two lines. Conclusion In summary, these results contribute to a deeper understanding of the overall mechanisms underlying artificial aging tolerance in sweet corn seeds. The findings of this study are expected to provide valuable insights for the storage of sweet corn seeds.